A cross‐sectional study of correlates of imprisonment in opioid‐dependent men and women in New South Wales, Australia. (29th December 2015) - Larney, Sarah; Cama, Elena; Nelson, Elliot; Larance, Briony; Degenhardt, Louisa
Abstract: Introduction and Aims: Involvement in the criminal justice system is common among opioid‐dependent people. This study aimed to determine prevalence and adolescent‐onset correlates of adult imprisonment among opioid‐dependent men and women in New South Wales, Australia. Design and Methods: Participants were recruited from opioid substitution therapy clinics and completed a face‐to‐face, structured interview. Data were collected on demographic characteristics, family history, substance dependence and psychiatric disorders. Adolescent‐onset correlates of adult incarceration (including interactions with gender) were examined using logistic regression. Results: Opioid‐dependent men were significantly more likely than opioid‐dependent women to report adult imprisonment (66% vs 40%; P  < 0.001). In a multivariable logistic regression model, older age, male gender, having completed high school education only, having dependent children or living independently prior to age 18 years, a history of juvenile detention and adolescent‐onset opioid dependence were all significantly associated with increased odds of adult imprisonment. Adolescent‐onset depression was associated with a halving of odds of adult imprisonment. The only variable for which we observed an interaction with gender was juvenile detention, which had a significantly greater impact on the odds of imprisonment for men than women. Discussion and Conclusions: More than half of this sample of opioid dependent adults had a history of imprisonment. Variables that are associated with imprisonment in the general population, such as childhood maltreatment, were not important in predicting imprisonment in this sample. Further study is required to understand the interaction between sex and juvenile detention in predicting adult imprisonment. [Larney S, Cama E, Nelson E, Larance B, Degenhardt L. A cross‐sectional study of correlates of imprisonment in opioid‐dependent men and women in New South Wales, Australia. Drug Alcohol Rev 2016;35:686‐692]